Qué cuidados necesita mi mascota para niños de 3 años - Izquierdo Ninaquispe, Lourdes Jhoana (2018)
The present work of professional sufficiency is based on the design of the class session with the competence communicates orally in their mother tongue and the performance expresses their needs, emotions, interests and reports on some experiences when interacting with people from their family environment, school or local. It uses frequently used words, smiles, looks, signs, gestures, body movements and various volumes of voice with the intention of achieving its purpose: to inform, ask, convince or thank. On the other hand, this session is based on the communicative approach that tells us that the communicative acts carried out in the classroom should be as true as possible and close to their daily reality. The inputs, the samples of Spanish with which one works, should be, as far as possible, authentic texts, both written and oral. Without forgetting that the extralinguistic component of communication must always be introduced: gestures, physical and visual contact, the distance between the interlocutors. For this, it is important to introduce the sociocultural aspect of the language, the so-called non-formal or lowercase culture. In this way, we will be able to work on intercultural competence while working the language. In other words, linguistic or grammatical competence is not enough to express oneself and understand a language if the user does not possess at the same time a pragmatic competence. Therefore, the acquisition of the system or the code of a language will be as important as the use made of that system in a given situation so that said use is appropriate to the communication situation.